2022
DOI: 10.1001/jamanetworkopen.2022.42964
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Use of Oral Anticoagulants in Older Adults With Newly Diagnosed Atrial Fibrillation, 2010-2020

Abstract: ImportanceUndertreatment of older adults with atrial fibrillation with anticoagulation therapy is an important practice gap. It has been posited that the availability of direct oral anticoagulants (DOACs) would improve oral anticoagulant (OAC) initiation in older adults with atrial fibrillation given their superior safety profile compared with warfarin.ObjectivesTo systematically examine trends in OAC initiation and nonadherence in older adults with atrial fibrillation and coexisting geriatric conditions.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 47 publications
2
53
0
Order By: Relevance
“…42 Studies in outpatient populations have found that frailty and geriatric syndromes are associated with decreased rates of anticoagulant prescription among older adults with atrial fibrillation. 5,12,15 Our study extends these findings to the inpatient setting. Although no prior US studies have examined inpatient anticoagulation by geriatric syndrome status, a meta-analysis of three small European studies that included a total of 1204 hospitalized patients found that frail older adults were less likely to receive an anticoagulant.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…42 Studies in outpatient populations have found that frailty and geriatric syndromes are associated with decreased rates of anticoagulant prescription among older adults with atrial fibrillation. 5,12,15 Our study extends these findings to the inpatient setting. Although no prior US studies have examined inpatient anticoagulation by geriatric syndrome status, a meta-analysis of three small European studies that included a total of 1204 hospitalized patients found that frail older adults were less likely to receive an anticoagulant.…”
Section: Discussionsupporting
confidence: 71%
“…Prior estimates using Medicare data have largely focused on the outpatient setting and demonstrate anticoagulant initiation rates for incident atrial fibrillation around 50%. 3,4,12,13,40 One recent study of patients in an integrated health system with incident inpatient atrial fibrillation associated with sepsis reported anticoagulant initiation rates of 20%. 41 Taken together with these studies, our results suggest that patients diagnosed with atrial fibrillation while admitted for other medical conditions-even those at high stroke risk-are infrequently initiated on anticoagulants or discharged with ambulatory cardiac monitors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations